Structural Racism, Dividing Line, Representations, Stereotype and Discrimination Against Afro-Peruvians in Advertising - Mendoza Cuéllar, Héctor José (2021)
The goal of this essay is to reflect on the different representations of Afro-descendant children, adolescents, and adults in Peruvian advertising. Thus, the following are proposed as guiding questions: How does advertising represent Afro-Peruvians? What role does it play in maintaining or changing these images? In this way, theoretical constructs such as racism, structural racism, dividing line, representation, stereotype and discrimination will be used to qualitatively analyze advertising spots for Peruvian trademarks broad-cast—in a time frame of approximately 10 years—on free-to-air television, and, in some cases, from the Internet. This essay does not seek to establish a canon. On the contrary, it is aware of its limitations, but questioning the role of advertising in the Afro-Peruvian struggle is a way to start a path to take a position and be an ally of change.